Protons, Photons, and the Prostate – Is There Emerging Evidence in the Ongoing Discussion on Particle Therapy for the Treatment of Prostate Cancer? - Schiller, Kilian C.; Habl, Gregor; Combs, Stephanie E. (Frontiers in Oncology, 2016)
Proton therapy is actively and repeatedly discussed within the framework of particle therapy for the treatment of prostate cancer. The argument in favor of treating the prostate with protons is partly financial: given that small volumes are treated, treat-ment times are low, resulting in a hypothetical high patient throughput. However, such considerations should not form the basis of medical decision-making. There are also physical and biological arguments which further support the use of particle therapy for prostate cancer. The only relevant randomized data currently available is the study by Zietman and colleagues, comparing a high to a low proton boost, resulting in a significant increase in PSA-free survival in the experimental (high-dose) arm. 1 With modern photon treatments and image guided radiotherapy (IGRT) equally high doses can be applied with photons, and thus a randomized trial comparing high-end photons to protons is warranted. For high-linear energy transfer (LET) particles, such as carbon ions, the increase in relative biological effectiveness (RBE) could potentially convert into an improvement in outcome. Additionally, through the physical differences of protons and carbon ions, the steeper dose gradient with carbon ions and the lack of beam broadening in the proton beam lead to a superior dose